Keragaman Fenotip Ikan Betok (Anabas testudineus Bloch) pada Perairan Rawa Gambut - Kartika Bungas (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2014)
The relation between 10 groups in 5 peat waters locations have the nearest relation that shown by the closeness between the groups in its spreading monometric character. There was founded 12 characters can be used as the model to distinguish the variety of Climbing perch. Actually, there were only 8 characters from 12 characters that have strong point to deceive the distinction of climbing perch morphology, which were, A1, A2, A4, B2, B5, C3, C5 and D3. The result of hierarchy analysis showed the biggest genetic range was happened between group 1 and group 3 with the numeric form is 0,078. The implication of that number was used to intersect between the groups or populations.